Cytogenetic findings and maternal age in patients with Down Syndrome at a tertiary level hospital in Bangladesh (Journal of Shaheed Suhrawardy Medical College, 2026)
Down syndrome is a common chromosomal disorder, related with multiple congenital anomalies with mental retardation. The cytogenetic profile of Down syndrome includes free trisomy 21, Robertsonian translocations, mosaicism, duplication of the DS critical region and other structural rearrangements involving chromosome 21.  Identification of various types of chromosomal abnormalities in Down syndrome is very important. It aids in management of these children and to aware the affected families about recurrence risk and options available. The objective of this study was to describe the cytogenetic alterations of patients with Down syndrome and their relationship with maternal age. In this cross-sectional analytical study, Karyotyping was done in 42 patients out of 103 clinically suspected DS cases. Among them, free trisomy (n=33; 78%) was most common followed by Robertsonian translocation (n=7; 17%) and mosaic trisomy (n=2; 5 %) respectively.  Majority of patients were males (n=30; 71.43%) and the male: female ratio was 5:2. Most (n=18; 43%) of patients with Down syndrome were born to mother age below 30 years, suggesting that there are other risk factors than advanced maternal age in this group.J Shaheed Suhrawardy Med Coll 2024; 16(2): 83-86